Design And Construction of A Website-Based Digital Printing Product Marketing System - Ahmad Wilda Nur Fajri; Tutik Khotimah; Ahmad Jazuli (International Journal of Science and Environment (IJSE), 2025)
The Web-Based Sales Information System at Inenndo Konveksi Printing is a modern solution for managing sales processes and data management in the printing industry. With increasing customer demand for printing services, the need for an efficient and integrated system is becoming increasingly important. This study aims to develop a web-based sales information system that enables Inenndo Konveksi Printing to improve operational efficiency, expand market reach, and enhance customer satisfaction. The system development method uses a web-based software development approach and a literary methodology using the waterfall method through the stages of system design requirements analysis, implementation, testing, and maintenance, with the Larafel framework. Various key features have been implemented in the system, including product management, online ordering, order tracking, inventory management, and sales reporting. Integration with an online payment system allows customers to make payments easily and securely. System evaluation was conducted through functional testing and collecting feedback from users. The evaluation results show that this system successfully meets the business needs of Inenndo Konveksi Printing and helps improve their operational efficiency. Customers also provided positive feedback regarding the system's ease of use and a pleasant online shopping experience. Overall, this Web-Based Sales Information System significantly improves Inenndo Konveksi Printing's business performance and strengthens its position in the competitive printing market. With the right technology, printing companies can leverage the full potential of web-based information systems to optimize their operations and meet evolving market demands.